The Implementation of P5 in Learning Science for Eighth Grade in Junior High School - Solikha, Regina Atya Gading Balgis; Anisa, Sri Wilujeng Toyibatul; Putri, Alisa Amanda; Mandarani, Vidya (Universitas Muhammadiyah Sidoarjo, 2024)
In this study which aims to analyze P5 activities at SMP Negeri 1 Wonoayu with the theme of local wisdom, which includes the preparation stage which provides findings that the Junior High School provides training to all teachers every month to develop their abilities, so that teachers at this Junior High School can implement P5 well. At the implementation stage, P5 activities at this Junior High School are carried out every Tuesday with different themes. This research uses a qualitative method using descriptive research. In collecting data, the techniques used were interviews, field observations and documentation of activities. Interviews were conducted to find out more in-depth things about P5 activities that could not be found through observation. Documentation includes notes during research, other documents, and photos as documents that support evidence of research implementation and to complement research data. The subject of this research is science learning in the independent curriculum. In obtaining the data through several school parties, namely the lead teacher, facilitator teacher and P5 team, and several students involved in the implementation of P5 activities. The data analysis technique used is the Milles and Huberman model in (Rijali, 2018). This research applies differentiated learning to the independent curriculum in obtaining data from the deputy principal, academy, facilitator teachers, as well as the P5 team, and several students involved in implementing P5 activities in the independent curriculum. The results of this study have a stage where the first stage of P5 implementation is carried out in two weeks where students are given material and practice democracy in the classroom and school scope. At the evaluation stage, the principal and facilitator hold a meeting that discusses the obstacles faced and provides solutions or reflections for the day of the P5 meeting. The second stage is the implementation of differentiation that has been successfully carried out for P5 activities in the content differentiation strategy, the problem process and also produces a product. The third stage in P5 activities that have been carried out as a form of differentiated learning in the independent curriculum has a good impact on character building, especially on students in democracy that is close to students in accordance with the profile of Pancasila students.